Strategic Pioneering And Its Connection To Faculty Members' Administrative Creativity At Palestinian And Jordanian Universities (Journal of Namibian Studies : History Politics Culture, 2023)
The study's goal is to comprehend strategic pioneering and its connection to administrative innovation among faculty members at universities in Palestine and Jordan.   The researchers used a descriptive-relational methodology with 146 faculty members as an accessible sample to accomplish the study's goals. The researchers developed a questionnaire to assess entrepreneurship. The researchers confirmed the psychometric properties of the approach and its relationship to administrative creativity among faculty members at Palestinian and Jordanian universities, which was composed of 35 paragraphs dispersed on two axes. The Jordanian University also issued several recommendations, the most important of which is that faculty members should learn to turn obstacles into opportunities that can be seized and that they should work to create a determined strategy to put the university's necessary strategies into action.